Humoral and Cellular Immune Response Elicited by mRNA Vaccination Against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in People Living With Human Immunodeficiency Virus Receiving Antiretroviral Therapy Based on Current CD4 T-Lymphocyte Count. (2nd April 2022) - Antinori, Andrea; Cicalini, Stefania; Meschi, Silvia; Bordoni, Veronica; Lorenzini, Patrizia; Vergori, Alessandra; Lanini, Simone; De Pascale, Lidya; Matusali, Giulia; Mariotti, Davide; Cozzi Lepri, Alessandro; Gallì, Paola; et al.
Abstract: Background: Data on SARS-CoV-2 vaccine immunogenicity in PLWH are currently limited. Aim of the study was to investigate immunogenicity according to current CD4 T-cell count Methods: PLWH on ART attending a SARS-CoV-2 vaccination program, were included in a prospective immunogenicity evaluation after receiving BNT162b2 or mRNA-1273. Participants were stratified by current CD4 T-cell count (poor CD4 recovery, PCDR: <200/mm 3 ; intermediate CD4 recovery, ICDR: 200–500/mm 3 ; high CD4 recovery, HCDR: >500/mm 3 ). RBD-binding IgG, SARS-CoV-2 neutralizing antibodies (nAbs) and IFN-γ release were measured. As control group, HIV-negative healthcare workers (HCWs) were used Findings: Among 166 PLWH, after 1 month from the booster dose, detectable RBD-binding IgG were elicited in 86.7% of PCDR, 100% of ICDR, 98.7% of HCDR, and a neutralizing titre ≥1:10 elicited in 70.0%, 88.2%, and 93.1%, respectively. Compared to HCDR, all immune response parameters were significantly lower in PCDR. After adjusting for confounders, current CD4 T-cell <200/mm3 significantly predicted a poor magnitude of anti-RDB, nAbs and IFN-γ response. As compared with HCWs, PCDR elicited a consistently reduced immunogenicity for all parameters, ICDR only a reduced RBD-binding antibody response, whereas HCDR elicited a comparable immune response for all parameters Conclusion: Humoral and cell-mediated immune response against SARS-CoV-2 were elicited in most of PLWH, albeit significantly poorer in those with CD4 T-cell <200/mm 3 versus those with >500 cell/mm 3 and HIV-negative controls. A lower RBD-binding antibody response than HCWs was also observed in PLWH with CD4 T-cell 200–500/mm 3, whereas immune response elicited in PLWH with a CD4 T-cell >500/mm 3 was comparable to HIV-negative population Abstract : Humoral and cell-mediated immune-response against SARS-CoV-2 were elicited in PLWH, significantly poorer in those with CD4 T-cell <200/mm 3 vs those with >500 cell/mm 3 and HIV-negative controls; immune response in PLWH with a CD4 T-cell >500/mm3 was comparable to HIV-negative population.